The primary growth of laryngeal squamous cell carcinoma cells in vitro is effectively supported by paired cancer-associated fibroblasts alone - Mei Wang; Chunping Wu; Yu Guo; Xiaojuan Cao; Wenwei Zheng; Guo-Kang Fan (Tumor Biology)
Most primarily cultured laryngeal squamous cell carcinoma cells are difficult to propagate in vitro and have a low survival rate. However, in our previous work to establish a laryngeal squamous cell carcinoma cell line, we found that laryngeal cancer-associated fibroblasts appeared to strongly inhibit the apoptosis of primarily cultured laryngeal squamous cell carcinoma cells in vitro. In this study, we investigated whether paired laryngeal cancer-associated fibroblasts alone can effectively support the growth of primarily cultured laryngeal squamous cell carcinoma cells in vitro. In all, 29 laryngeal squamous cell carcinoma specimens were collected and primarily cultured. The laryngeal squamous cell carcinoma cells were separated from cancer-associated fibroblasts by differential trypsinization and continuously subcultured. Morphological changes of the cultured laryngeal squamous cell carcinoma cells were observed. Immunocytofluorescence was used to authenticate the identity of the cancer-associated fibroblasts and laryngeal squamous cell carcinoma cells. Flow cytometry was used to quantify the proportion of apoptotic cells. Western blot was used to detect the protein levels of caspase-3. Enzyme-linked immunosorbent assay was used to detect the levels of chemokine (C-X-C motif) ligand 12, chemokine (C-X-C motif) ligand 7, hepatocyte growth factor, and fibroblast growth factor 1 in the supernatants of the laryngeal squamous cell carcinoma and control cells. AMD3100 (a chemokine (C-X-C motif) receptor 4 antagonist) and an anti–chemokine (C-X-C motif) ligand 7 antibody were used to block the tumor-supporting capacity of cancer-associated fibroblasts. Significant apoptotic changes were detected in the morphology of laryngeal squamous cell carcinoma cells detached from cancer-associated fibroblasts. The percentage of apoptotic laryngeal squamous cell carcinoma cells and the protein levels of caspase-3 increased gradually in subsequent subcultures. In contrast, no significant differences in the proliferation capacity of laryngeal squamous cell carcinoma cells cocultured with cancer-associated fibroblasts were detected during subculturing. High level of chemokine (C-X-C motif) ligand 12 was detected in the culture supernatant of cancer-associated fibroblasts. The tumor-supporting effect of cancer-associated fibroblasts was significantly inhibited by AMD3100. Our findings demonstrate that the paired laryngeal cancer-associated fibroblasts alone are sufficient to support the primary growth of laryngeal squamous cell carcinoma cells in vitro and that the chemokine (C-X-C motif) ligand 12/chemokine (C-X-C motif) receptor 4 axis is one of the major contributors.